De quelques aspects de la responsabilité professionnelle du courtier d’assurance - Dalpé, Jean (Assurances, 1987)
Some parties have tried to invoke the insurance broker's liability for business placed with a bankrupt insurer. A broker is familiar with the market and hence knows which companies have the most solid footing. However, certain circles contend that if a broker directs a client to a company which eventually is winded up, the former must assume his share of the client's fosses. This is a serious question which Mr. Dalpé addresses by bringing to light many reasons which debunk this statement, except in specific cases involving negligence or professional fault.